Does Deliberative Education Increase Civic Competence? Results from a Field Experiment. Issue 3 (15th October 2020) - Persson, Mikael; Andersson, Klas; Zetterberg, Pär; Ekman, Joakim; Lundin, Simon
Abstract: How should education be structured to most effectively increase civic outcomes such as political knowledge and democratic values? We present results from a field experiment in which we compare the effects of deliberative education and traditional teacher-centered education. The study is the largest field experiment on deliberative education to date and involved more than 1, 200 students in 59 classrooms. We test the effects on four forms of civic competence: political knowledge, political interest, democratic values, and political discussion. In contrast to previous research, we find little evidence that deliberative education significantly increases civic competence.